PHYSICAL AND ENGINEERING PROPERTIES OF PEAT SOIL STABILIZED WITH THE ADMIXTURE OF CACO3+RICE HUSK ASH DUE TO WATER INFILTRATION FROM SURROUNDING AREAS: peat soil stailization - Yulianto, Faisal Estu; Mochtar, Noor Endah; Afif, M Ma'ruf (Journal of Applied Engineering Science, 2022)
Peat is a type of soil with high organic content, very low bearing capacity, and high uneven settlement. Some methods to improve soil have been applied to peat in order to make it strong enough for civilization-building foundation situated on it. Peat stabilization is a method that is continuously developed considering that the cost it needs is lower and this approach is more environmentally friendly compared to other methods. The admixture of lime (CaCO3) and Rice husk ash, a new ecofriendly stabilizer material, has been applied to peat soil and showed a good result. However, in studies conducted previously, the effect of water infiltration from surrounding areas of soil was stabilized was not involved as variable influencing the change of parameter. Based on that, this laboratory study was carried out to model the real condition in the field when the stabilization is performed and to identify the physical and engineering changes of peat soil in the 10th, 20th, and 30th days of stabilization in its border and middle parts, with the percentage of material stabilizer 5%, 10%, 15% and 20% of the unit weight of the initial condition of peat. The result of laboratory test shows that the addition of admixture of lime (CaCO3) and rice husk ash can improve the physical and engineering properties of peat soil are stabilized. Water infiltration occurred on peat soil is stabilized has not affected the physical and engineering properties of the soil. It can be seen from the physical and engineering properties of the border and central parts of peat soil is stabilized that still have a similar value. It is assumed to be caused by CaSiO3 gel formed still needs a longer duration to become stable gel. However, in this initial study it was known that the more stabilizers added, made the better the parameters of the stabilized peat soil.
Keywords: stabilization, peat soil, lime, rice husk ash, water infiltration